PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DALAM KEPEMILIKAN KTP ELEKTRONIK PADA KELURAHAN CEMPAKA BARU - Andi Putri Djohar Tenri Waru; Yunita Janah; Inggit Dessy Susanti; Sheilla Risma Yanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This study focuses on the quality of public services with the aim is to find out how much influence and what variables are most influential on society satisfaction. This research uses quantitative descriptive method the type of research used is survey which afterwards the result is processed by using SPSS 24. The research location is conducted in Cempaka Baru, Central Jakarta. The population used is the society of Kelurahan Cempaka Baru who already has E-KTP. Determination of samples using Slovin formula with 5% tolerance to get as many as 101 respondens from a total of 676 popoulation in Kelurahan Cempaka Baru. The research got result that the satisfaction ofsociety have positive influence simultaneously by the five service quality variables which include tangible (X1), reliability (X2), responsiveness (X3), assurance (X4) and emphaty (X5). The correlation and dtermination test results are in strong relationship of 0.623 with an influence level of 38.8%, while the remaining 61.6% is explained by other variable not examined in this study. Of the five variables, tangible variables have a partial influence in Kelurahan Cempaka Baru of 8,733